Design and development of an automated temperature controller for curing ovens - Schoeman, Ruaan Mornè (My University, 2012)
Curing of materials in order to obtain different properties has been a practice for many years. New developments in composite materials increase the need to control certain variables during the curing process. One very significant variable is temperature. Temperature control by itself is an old practice, however when the need for repeatedly controlling the process accurately over long periods of time arises, a system is required that outperforms normal manual control. One of the aspects within such a system that needs to be considered is the ability to replicate the temperatures within an oven which were originally used for a specific material’s curing profile. This means that a curing profile would need to be defined, saved for later and finally be interpreted correctly by the controlling system. Different control methods were simulated to enable the system to control the temperature which has been defined by literature. This dissertation introduces a variation on the standard control methods and shows improved results. Switching the oven on and off in order to increase or decrease internal oven temperature seems simple, but can cause switching devices to decrease their operational life span, if not designed carefully. A combination switch was introduced which harnesses the advantages of two very common switching devices to form an improved combination switch. Software for the personal computer environment, as well as software for the embedded environment were developed and formed a control system that produced acceptable results for temperature control. Accuracies of 98% and more were achieved and found to be acceptable according to standard engineering control practices. An accurate temperature profile controller was designed, simulated and built in order to control the temperature inside a specific curing oven which, in turn, determined the curing properties of specific materials. The overall results were satisfactory which lead to achieving the objectives outlined in this dissertation.
Thesis (M. Tech. - Engineering: Electrical, Department Electronic Engineering, Faculty of Engineering and Technology)--Vaal University of Technology.
Keywords: Materials -- Curing; Composite materials -- Curing; Curing -- Temperature control; Curing ovens -- Temperature control; Temperature control -- Computer software; Oven temperature control -- Switching devices; 621.317; Materials -- Effect of temperature on; Composite materials -- Curing; Heat engineering -- Instruments.